Analisa Nilai Kuat Tekan dan Kuat Lentur Terhadap Tambah Polypropylene Fiber Curved Form Pada Campuran Beton Normal - Risayanti, Risayanti; Triwahyudi, Raja Nurrahman; Anggraini, Rita (Jurnal Civronlit Unbari, 2023)
The increase in the need for building material of concrete for infrastructure need to be improved through technology inovation. Various methods have been developed to increase the compressive strength and flexural strength of concrete, one of them by adding micro reinforcement such as fiber. In this research, polypropylene fiber curved form is used. This research aims to analyze the influence of adding fiber into the design concrete mix on their compressive and fexible strength. In this study, the mix design used the SNI 7656-2012 method and the design compressive strength is 30 Mpa, the design slump height is 70 mm – 100 mm. Normal concrete is added with polypropylene with the composition of 3 kg/m3, 4 kg/m3, 5 kg/m3. 24 cylinder (15 x 30 mm) test objects are provided, and 24 beam (15 x 15 x 60 cm) test objects are provided, with 3 tests for each variety for the age of 7 and 28 days. Based on the test the compression strength results of normal concrete for the age of 28 days are obtained as 35.19 Mpa. Optimum value is obtained in the variety of 4 kg/m3, in the age of 7 days as 31,88 MPa or 15,74% increase, in the age of 28 days as 40.94 MPa or 16.33% increase from the normal concrete compressiven strength. The flexural strength of normal concrete aged 28 days is found to be 4.76 Mpa. The optimum value of flexible strength with the variety of 4 kg/m3, in the age of 7 days is obtained as 4,76 Mpa or 5,76% increase, in the age of 28 days is obtained as 5.87 Mpa or increase of 23.26% from the flexible force of normal concrete. Based on the results of this research, the adding of polypropylene fiber into the concrete mix can increase its mechanical properties, mainly the compression and flexible strength.